CHARACTERIZATION OF EARLY CAULIFLOWER GERMPLASM UNDER TROPICAL CONDITIONS - M. SANTHOSHA,; B. VARALAKSHMI,; K. S. SHIVASHANKARA, (The Bioscan, 2014)
The present investigation was undertaken to morphologically characterize the 51 genotypes of cauliflower for various horticultural characters. Out of 51 early cauliflower genotypes characterized, high coefficient of variation (C.V) was observed for yield characters like, gross curd weight (26.03 %), net curd weight (26.02 %) followed by curd size index (24.95 %) suggesting that these traits should be given top priority during selection programme. Genotypes viz., IIHR-272, IIHR-263, IIHR-266 and IIHR-390 showed superior performance for above parameters, hence these lines may be directly used for cultivation or as a source of desirable traits in a breeding programme for the improvement of curd yield and quality in cauliflower.